Infantile osteomyelitis of the fourth rib causing the occurrence of a lung abscess. Issue 7 (28th May 2019) - Mori, Sayo; Onoyama, Sagano; Takimoto, Tomoko; Morooka, Yuya; Furuno, Kenji
Abstract: Infantile osteomyelitis of the rib is rare but can be complicated by intrapleural pyogenic lesions. Even if findings suggest another infection focus, osteomyelitis should be considered if there are changes on radiographs. In addition, it can be prevented by maintaining the dermal barrier function through skin care. Abstract : Infantile osteomyelitis of the rib is rare but can be complicated by intrapleural pyogenic lesions. Even if findings suggest another infection focus, osteomyelitis should be considered if there are changes on radiographs. In addition, it can be prevented by maintaining the dermal barrier function through skin care.